GESTÃO DO CONHECIMENTO NA ORGANIZAÇÃO: UM ESTUDO TEÓRICO COMO BASE PARA PROPOSIÇÃO DE UM MODELO - Oliveira, Giane Lise de A. (2013)
The new company considers knowledge as a strategic resource for their organizations . The sheer volume of information that is delivered through a variety of means has led organizations to reflect on what strategies should be adopted to continue succeeding in this modern world and so competitive , where information and knowledge are considered high- value goods . This research deals with knowledge management in the organization and was made a theoretical study as a basis to propose a model of knowledge management to collaborate for the growth and development of enterprises . The literature makes it clear that the traditional ways of managing companies are proving inadequate and new forms of governance are emerging . The consequences have emerged in the strategies , management practices and organizational technologies and lead to new theories of knowledge management . This study focuses on the themes of the different approaches to knowledge as well as their classification, creation and implementation within the organization . Sharing / transfer of knowledge , together with the organizational and cultural learning organization is another topic covered , with key components of knowledge management systems . It is considered important that employees are motivated to share their experiences with their colleagues based on trust and mutual respect. The study discussed the theoretical model , their interaction with the organizational culture and the implications for the effectiveness of the organization . Change always happens with a person and that this knowledge is valued within the organization needs to be shared with everyone. Work on the basis of qualitative research , whose means were bibliographic , descriptive in nature , where the methodological procedures involve research , analysis, synthesis and systematization of ideas from relevant literature was used .